IMPLEMENTATION OF A TARGETED MODEL OF TESTING ROLLING STOCK COMPONENTS - Гребенюк, Владислав; Гребенюк, Сергій; Український, Євген; Лямзін, Андрій (SWorldJournal, 2025)
The paper considers an adapted mechanism for assessing the performance of rolling stock components. The specified mechanism is based on the “two-bath” method and is aimed at determining the functionality of components from the point of view of the influe